Change(s) in Vocabulary(/ies) – Hungarian and Romanian Lexical Phenomena During COVID - Enikő Biró; Gabriella Kovács; Imola Katalin Nagy (Acta Universitatis Sapientiae: Philologica)
The COVID-19 epidemic caused not only an unprecedented crisis in our lives but also changes in our language use and word formation habits: this new disease and its cures have naturally led to the emergence of new concepts and names. In 2020, more and more words or phrases related to the COVID-19 epidemic appeared in the public sphere as a result of COVID-related publications issued by the World Health Organization, regulations issued by the authorities of the countries, news in the press, and endless debates in the social media. This study examines the lexicalization processes and semantic shifts generated by the COVID epidemic, as we aim to examine professional and colloquial developments in pandemic-inspired terminology. We analyse the changes that have taken place in the Hungarian and Romanian language environment, while also taking into account the English language elements as a background reference. Among the most notable lexico-semantic phenomena, we have identified word coinages, changes of meaning, and varied word formation techniques which have fostered the processes of lexicalization and neologism creation, revealing an impressive linguistic dynamic at the level of public discourse.